DEBT MARKET TIMING: EVIDENCE FROM BANK-BASED SYSTEMS - Bougatef, Khemaies; Chichti, Jameleddine (Journal of Advanced Studies in Finance; Vol 1 No 2 (2010): JASF Volume I Issue 2 Winter 2010, 2010)
Several studies make evidence that market timing becomes the factor that shapes financing policies. However, debt market timing still less developed compared to equity market timing. This paper investigates the relevance of market timing considerations on the debt issuance using a panel of 30 Tunisian listed firms and 100 French firms of the stock market index SBF 120. Consistent with the market timing theory, we find that firms tend to issue debt when interest rate are low and are less likely to take debt issuance decisions when they perceive equity market conditions as more favourable. This evidence suggests that borrowing policies are shaped by market timing considerations.